1999
DOI: 10.1016/s0028-3908(99)00058-1
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine inhibits L-type Ca2+ channels in cultured rat hippocampal neurons stimulated with glutamate receptor agonists

Abstract: In order to better understand the mechanism(s) of action of carbamazepine (CBZ), we studied its effects on the increase in [Ca 2 + ] i and [Na + ] i stimulated by glutamate ionotropic receptor agonists, in cultured rat hippocampal neurons, as followed by indo-1 or SBFI fluorescence, respectively. CBZ inhibited the increase in [Ca 2 + ] i stimulated either by glutamate, kainate, a-amino-3-hydroxy-5-methyl-isoxazole-4-propionate (AMPA), or N-methyl-D-aspartate (NMDA), in a concentration-dependent manner. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 46 publications
6
37
0
1
Order By: Relevance
“…Calcium entering through L-type calcium channels may play a role in activity-dependent gene expression and synaptic plasticity. Some AEDs (such as carbamazepine) have been proposed to antagonise L-type calcium channels but the relevance of this to their antiepileptic effect is unclear [Ambrosio et al 1999]. N-and P/Q-type channels are expressed at synaptic boutons where they mediate calcium entry necessary for neurotransmitter release.…”
Section: Calcium Channelsmentioning
confidence: 99%
“…Calcium entering through L-type calcium channels may play a role in activity-dependent gene expression and synaptic plasticity. Some AEDs (such as carbamazepine) have been proposed to antagonise L-type calcium channels but the relevance of this to their antiepileptic effect is unclear [Ambrosio et al 1999]. N-and P/Q-type channels are expressed at synaptic boutons where they mediate calcium entry necessary for neurotransmitter release.…”
Section: Calcium Channelsmentioning
confidence: 99%
“…Hippocampal neurons were dissociated from hippocampi of E18 -E19 rat embryos, as previously described (Ambró sio et al, 1999) and cultured in serum free Neurobasal medium (GIBCO, Life Technologies, UK) with B27 supplement (GIBCO), 25 M glutamine, 0.5 mM glutamate and 0.12 mg/ml gentamicin. Cultures were plated on poly-D-lysine-coated (0.1 mg/ml) glass coverslips at a density of 0.2ϫ10 6 cells/cm 2 and kept at 37°C in a humidified incubator in 5% CO 2 /95% air for 7-8 days, the time required for maturation of hippocampal neurons.…”
Section: [ 3 H]adenosine Release Studiesmentioning
confidence: 99%
“…We have previously shown that VSCCs, mainly L-and N-type Ca 2+ channels, have a predominant role in the [Ca 2+ ] i changes evoked by kainate in cultured hippocampal neurons measured in cell populations [13]. The [Ca 2+ ] i responses evoked by kainate have a high degree of variability among individual hippocampal neurons [14], which is likely due to a differential expression of AMPA and kainate receptors.…”
Section: Introductionmentioning
confidence: 99%